The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/aem.00080-17
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quorum-Quenching N -Acylhomoserine Lactone Acylase from Acidovorax sp. Strain MR-S7 Mediates Antibiotic Resistance

Abstract: N-Acylhomoserine lactone acylase (AHL acylase) is a well-known enzyme responsible for disrupting cell-cell communication (quorum sensing) in bacteria. Here, we isolated and characterized a novel and unique AHL acylase (designated MacQ) from a multidrug-resistant bacterium, Acidovorax sp. strain MR-S7. The purified MacQ protein heterologously expressed in Escherichia coli degraded a wide variety of AHLs, ranging from C6 to C14 side chains with or without 3-oxo substitutions. We also observed that AHL-mediated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 35 publications
(49 reference statements)
5
71
0
Order By: Relevance
“…The expression of macQ isolated from Acidovorax sp. strain MR-S7 was performed using Escherichia coli cells, as previously described 3 . The precursors of AHL-acylases and related enzymes are cleaved into three polypeptide chains (α-chain, internal SP, and β-chain) and the catalytically active mature enzymes are generated as a heterodimer consisting of α- and β-chains, with the SP being released 30 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The expression of macQ isolated from Acidovorax sp. strain MR-S7 was performed using Escherichia coli cells, as previously described 3 . The precursors of AHL-acylases and related enzymes are cleaved into three polypeptide chains (α-chain, internal SP, and β-chain) and the catalytically active mature enzymes are generated as a heterodimer consisting of α- and β-chains, with the SP being released 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Acidovorax sp. strain MR-S7 is a gram-negative bacterium that was isolated from activated sludge in a treatment system for penicillin G-polluted wastewater 1 3 . We previously reported that Acidovorax sp.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations